Organizational Commitment as Moderator of Adaptability and Loyalty on In-Role Behavior among Gen Z’s Female Employees Worked in Manufacturing - Hajar Asna; Ariston Edward Aritonang; Dedi Muhammad Siddiq; James Tembo (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2026)
The aim of this study is to examine how adaptability and loyalty influence in-role behavior among Generation-Z female employees in the manufacturing sector, with organizational commitment as a moderating variable. Grounded in behavioral and organizational psychology concepts, this study highlights adaptability and loyalty as key employee attributes in today’s dynamic work environment. A quantitative approach was employed using a survey method, with data collected from 217 respondents. The data were analyzed using Structural Equation Modeling (SEM) via SmartPLS 4. The results indicate that both adaptability and loyalty have a positive and significant impact on in-role behavior. Furthermore, organizational commitment is found to strengthen these relationships. The implications of these findings suggest that human resource management should prioritize the development of adaptability, loyalty, and organizational commitment to enhance employee performance and responsiveness in the evolving manufacturing sector, particularly among Generation-Z females.